(3GdGOGQI GdeMdjI ai bWQ (B/ s - (3fhGQ GHQGgje UbQ GdeQjNis; (3LGHQ LGO fUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3JfbSe OQGSJfG gPI Gdi eHMK JegjOi h aUhd KdGKI h NGJeI aGeG GdeHMK GdGhd fJcde Yf JYQja h GQcGf GddGeQcRjI h ai GdaUd GdKGfi JfXQ Gdi GdGOGQI GdeMdjI ai eUQ GeG ai GdaUd GdKGdK h GdGNjQ afJfGhd aji GdGOGQI GdeMdjI ai bWQ Ke jYbH gPG cdI NGJeI fLed ajgG YfGUQ GdHMKs
(3jTJed Ydi edGMbs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2007s
(3HHdjhLQGajG(B: (3UaMGJ (B224-228s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3GdSdWI GdeQcRjIs; (3GdgjFGJ GdeMdjIs; (3GdEOGQI GdeMdjI aj eUQs; (3GdeLdS GdTYHj GdeMdjs; (3GdEOGQI GdeMdjI aj bWQs; (3GNJUGUGJ GdeLGdS GdTYHjI GdeMdjI s; (3GdeLdS GdHdOj GdeQcRj s; (3GNJUGUGJ GdeLdS GdHdOj GdeQcRj s; (3aj VhA GdbGfhf Qbe (B12 (3dSfI (B1998s; (3GdTNUjI GdGYJHGQjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3dbGfhf GdYGes